Transborder Links and Formal Education of Urban Youth on the Northern Border - Vargas-Valle, Eunice D. (Frontera Norte, 2017)
This article uses the Population and Housing Census 2000 to analyze the association between the post-basic education of the urban youth population and two indicators of transborder links on Mexico’s northern border: being born in the United States and having transmigrants at home. The multivariate statistical analysis shows that although being born in the United States is positively associated with attending and completing high school, living in households with transmigrants reduces the likelihood of continuing higher education. Despite the improved socio-economic status of transborder families, household members’ transborder employment may be affecting young people’s educational aspirations, since it proves that a higher relative income can be achieved without investing in higher education. Resumen Con base en el Censo de Población y Vivienda 2000, en este artículo se analiza el vínculo entre la educación pos-básica de la población joven urbana y dos indicadores de los nexos transfronterizos en la frontera norte de México: haber nacido en Estados Unidos y tener transmigrantes en el hogar. El análisis estadístico multivariado muestra que mientras el nacimiento en Estados Unidos se asocia positivamente a cursar y terminar la media superior, vivir en hogares con transmigrantes disminuye la posibilidad de continuar en estudios superiores. A pesar de la mejor situación socioeconómica de las familias transfronterizas, el empleo transfronterizo de los miembros del hogar podría estar afectando las aspiraciones educativas de los jóvenes, al demostrar que se pueden lograr mayores ingresos relativos, sin hacer inversiones en educación superior.